Improved Surgical Success of Combined Glaucoma Tube Shunt and Retisert® Implantation in Uveitic Eyes: A Retrospective Study. Issue 2 (December 2015) - Moore, Daniel; Stinnett, Sandra; Jaffe, Glenn; Asrani, Sanjay
Abstract Introduction The purpose of this study was to determine whether the outcomes following placement of a fluocinolone acetonide implant (Retisert® ; Bausch & Lomb, Inc.) combined with an Ahmed™ glaucoma valve (New World Medical, Inc.) in eyes with uveitic glaucoma (UG Retisert) were different when compared to an Ahmed valve alone in eyes with uveitic glaucoma or primary open angle glaucoma (UG non-Retisert and POAG, respectively). Methods Retrospective, interventional study of consecutive uveitic and OAG eyes undergoing Ahmed valve (AV) implantation with or without combined Retisert insertion at a single academic center between 2009 and 2012. Surgical success was defined as intraocular pressure (IOP) between 5 and 18 mmHg and greater than 20% reduction of IOP at two consecutive visits without need for additional IOP-lowering medications or surgical procedures. Secondary outcome measures included IOP and number of glaucoma medications. Results Sixty eyes of 60 patients (22 UG Retisert, 16 UG non-Retisert, 22 POAG) were included. Mean ± standard deviation surgical success duration was significantly greater in UG Retisert eyes, 629 ± 53 days, compared to those with UG non-Retisert, 361 ± 37 days, and POAG, 472 ± 65 days (P  = 0.034). At 24 months, the mean IOP was 11.7, 12.1, and 15.0 mmHg and the average patient was on 1.45, 0.71, and 2.00 medications in the UG Retisert, UG non-Retisert, and POAG valve groups, respectively. Conclusion Retisert implants when combined with AV in uveitic glaucoma had a longer duration of surgical success than uveitic or POAG treated with AV insertion alone.